PENGARUH STRUKTUR AKTIVA, RETURN ON ASSETS DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BURSA EFEK INDONESIA TAHUN 2011 – 2015 - Annie Chandra; Wenny Tantoni; Windy Villany; Mahmuddin Syah Lubis; Faisal Akbar (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
The purpose of the research is to analyze the effect of Assets Structure, Return On Assets and Growth of Sales on Capital Structure at Property and RealEstate Companies in Indonesia Stock Exchange year of 2011-2015. The research used some theories relating to Assets Structure, Return On Assets, Growth of Sales and Capital Structure. The approach of this research was quantitative. This type of research is descriptive explanatory. Populations in this research are 53 companies of Property and RealEstate in the Indonesia Stock Exchange in the year of 2011-2015. The result of the research samples were 25 companies of Property and RealEstate in the Indonesia Stock Exchange in the year of 2011-2015. The result of the research stated that partially Assets Structure had a negative significant effect on Capital Structure, Partially Return On Assets did not have a significant effect on Capital Structure, Partially Growth of Sales did not have a significant effect on Capital Structure at Property and RealEstate companies in Indonesia Stock Exchange in the year of 2011-2015. Simultaneously, Assets Structure, Return on Assets and Growth of Sales had a significant effect on Capital Structure at Property and Real Estate in Indonesia Stock Exchange in the year of 2011-2015.